INFLUÃŠNCIA DA ADUBAÃ‡ÃƒO MINERAL NA ORGANOGRAFIA DE RIZOMAS DE HEDÃQUIO AMARELO (Hedychim gardnerianum SHEPPARD EX. KER-GAWL) - Rochelle, Luiz Antonio; GonÃ§alves, Antonio Luiz; Lucchesi, Antonio Augusto; Minami, Keigo (REVISTA DE AGRICULTURA, 2015)
INFLUÃŠNCIA DA ADUBAÃ‡ÃƒO MINERAL NA ORGANOGRAFIA DE RIZOMAS DE HEDÃQUIO AMARELO (Hedychim gardnerianum SHEPPARD EX. KER-GAWL)